Retiform hemangioendothelioma of the breast in a man with 18F-flurodeoxyglucose accumulation on positron emission tomography: a case report - Kaoru Ogura; Yoko Shibasaki; Satoshi Honda; Hidetaka Akita; Nobuhiko Aoki; Ja-Mun Chong; Toru Motoi (Surgical Case Reports, 2023)
Abstract Background Retiform hemangioendothelioma (RH) is a rare, intermediate-grade vascular tumor that often arises in the trunk and extremities. The clinical and radiological features of RH remain largely unknown. Case presentation A male patient in his 70s presented with shortness of breath on exertion, and computed tomography incidentally revealed a tumor in his right breast. Positron emission tomography (PET) revealed moderate 18F-fluorodeoxyglucose (FDG) uptake in the tumor. RH was observed in the resected specimens. Three months after surgery, the patient was free of local recurrence and distant metastasis. Conclusions RH was found in the male breast and was accompanied by FDG uptake on PET. PET may be useful in diagnosing RH. Although metastasis is rare in RH, local recurrence may occur, and careful follow-up is required.